Thermally-activated Mactra veneriformis shells for phosphate removal in aqueous solution - Lee, Yeon Jin; Lee, Jae In; Lee, Chang Gu; Park, Seong Jik (Membrane and Water Treatment, 2023)
This study explored the feasibility of calcium-rich food waste, Mactra veneriformis shells (MVS), as an adsorbent for phosphate removal, and its removal efficiency was enhanced by the thermal activation process. The CaCO3 in MVS was converted to CaO by thermal activation (>800 °C), which is more favorable for adsorbing phosphate. Thermal activation did not noticeably influence the specific surface area of MVS. The MVS thermally activated at 800 °C (MVS-800), showed the highest phosphate adsorption capacity, was used for further adsorption experiments, including kinetics, equilibrium isotherms, and thermodynamic adsorption. The effects of environmental factors, including pH, competing anions, and adsorbent dosage, were also studied. Phosphate adsorption by MVS-800 reached equilibrium within 48h, and the kinetic adsorption data were well explained by the pseudo-first-order model. The Langmuir model was a better fit for phosphate adsorption by MVS-800 than the Freundlich model, and the maximum adsorption capacity of MVS-800 obtained via the Langmuir model was 188.86 mg/g. Phosphate adsorption is an endothermic and involuntary process. As the pH increased, the phosphate adsorption decreased, and a sharp decrease was observed between pH 7 and 9. The presence of anions had a negative impact on phosphate removal, and their impact followed the decreasing order CO32- > SO42- > NO3- > Cl-. The increase in adsorbent dosage increased phosphate removal percentage, and 6.67 g/L of MVS-800 dose achieved 99.9% of phosphate removal. It can be concluded that the thermally treated MVS-800 can be used as an effective adsorbent for removing phosphate
Keywords: Adsorbent dosage; Food waste; Langmuir models; Phosphate adsorption; Phosphate removal; Removal efficiencies; Seashell; Thermal activation; Thermal activation process; Thermally activated; adsorption; calcination; phosphorus; seashell; thermal activation